One immune system plays many parts: The dynamic role of the immune system in chronic pain and opioid pharmacology. (1st May 2023) - Mustafa, Sanam; Bajic, Juliana E.; Barry, Benjamin; Evans, Samuel; Siemens, Kariel R.; Hutchinson, Mark R.; Grace, Peter M.
Abstract: The transition from acute to chronic pain is an ongoing major problem for individuals, society and healthcare systems around the world. It is clear chronic pain is a complex multidimensional biological challenge plagued with difficulties in pain management, specifically opioid use. In recent years the role of the immune system in chronic pain and opioid pharmacology has come to the forefront. As a highly dynamic and versatile network of cells, tissues and organs, the immune system is perfectly positioned at the microscale level to alter nociception and drive structural adaptations that underpin chronic pain and opioid use. In this review, we highlight the need to understand the dynamic and adaptable characteristics of the immune system and their role in the transition, maintenance and resolution of chronic pain. The complex multidimensional interplay of the immune system with multiple physiological systems may provide new transformative insight for novel targets for clinical management and treatment of chronic pain. This article is part of the Special Issue on "Opioid-induced changes in addiction and pain circuits". Graphical abstract: Noxious stimuli results in upregulation of pro-inflammatory cytokines, chemokines or inflammatory mediators which initiate peripheral nociceptor activation. (1) Repeated stimuli results in recruitment of immune cells (PBMCs) to the injury site. (2) Repeated stimuli and immune signals from the region result in hyperexcitation of peripheral nociceptors leading to peripheral sensitization. (3) Recruitment of peripheral macrophages and (4) upregulation of TLR4 in the dorsal root ganglia play key roles in the development/maintenance of peripheral sensitization. Classical immune receptors, such as (5) FcγR1 are expressed on immune cells, dorsal root ganglia and neurons and play critical roles in regulating immunity and pro-nociceptive signaling, including chronic pain states. Peripheral sensitization and the immune-mediated interactions at the DRG/trigeminal ganglia level lead to maladaptive responses in the spinal cord and higher order brain regions. (6) Microglia and (7) astrocytes in the spinal dorsal horn detect danger signals from the periphery and transforming into their reactive phenotypes causing subsequent (8) release of pro-inflammatory cytokines, chemokines and mediators playing a pivotal step in the initiation of central sensitization. (9) TLR4 are upregulated in dorsal spinal cord (9a) microglia and (9 b) astrocytes. (10) Astrocytes mediate synaptic transmission modulation which contributes to the sensitization of second order nociceptive neurons. Image 1 Highlights: Neuroimmune interactions drive structural adaptations in neural circuits. Classical immune factors alter excitability of neurons via inflammatory independent mechanisms. Inflammatory signaling plays a role in injury resolution.